Christianity and Women's Education: Anna Maria van Schurman and Mary Astell - Duran, Jane (Philosophy & theology, 2014)
A contrast is developed between the educational views of van Schurman and Astell, revolving around their sense of Christian piety and their stance on women’s place in the social and political sphere. The work of Irwin, Hill, and others is cited, and it is concluded that important differences between the views of the two thinkers can be delineated, and that doing so helps us to understand the intellectual and philosophical milieu of the seventeenth century. In addition, the debate sheds light on today’s gender-essentialism controversies in education, and the extent to which intellectual rationality is a general human virtue.